Formulation of Gambir Extract Nanoemulgel with Maggot Oil as Oil Phase - Syifa Annaura; Irfan Yogik Ferdianiko; Akhfas Faisal Amin; Mayu Rahmayanti; Ria Indah Lestari; Dhia Fadhilah Salsabila (LPPM, Institut Teknologi Sepuluh Nopember, 2022)
AbstractGambir is the result of extraction from the leaves of the gambier plant (Uncaria gambir Roxb)which contains polyphenolic compounds. The polyphenolic compounds contained in this gambier extract are catechins which act as antimicrobials and antioxidants. The nanoemulgel formulationin this study used an active ingredient, namely gambir extract (Uncaria gambir Roxb) with a concentration of 9% containing flavonoids which have good antibacterial activity. In the manufacture of oil phase nanoemulsions from the use of 1% Black Soldier Fly (BSF) maggot oilwhich has characteristics such as VCO which is commonly used. Emulsification method wascarried out using a magnetic stirrer with a spontaneous mixing technique. Several nanoemulsion characterization tests using the Particle Size Analyzer (PSA) included particle size, polydispersityindex, and zeta potential results obtained according to the nano criteria, namely 382.27 ± 72.28 nm, 0.29 ± 0.14, respectively. and -0.57 ± 1.28 mV. In the nanoemulgel formulation of gambir extract, several tests were carried out such as organoleptic, homogeneity, pH (6.23 ± 0.31),dispersion (5.83 ± 0.15 g.cm/s), and adhesion (7.33 ± 0.90 s) that meet the criteria for nanoemulgel preparations.Keywords: Gambir extract; maggot oil; nanotechnology.